2019
DOI: 10.3171/2018.5.jns18976
|View full text |Cite
|
Sign up to set email alerts
|

Software-based simulation for preprocedural assessment of braided stent sizing: a validation study

Abstract: OBJECTIVEThe authors sought to validate the use of a software-based simulation for preassessment of braided self-expanding stents in the treatment of wide-necked intracranial aneurysms.METHODSThis was a retrospective, observational, single-center study of 13 unruptured and ruptured intracranial aneurysms treated with braided self-expanding stents. Pre- and postprocedural angiographic studies were analyzed. ANKYRAS software was used to compare the following 3 variables: the manufacturer-given nominal length (NL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…Commercially available software with embedded geometrical deployment methods include Sim&Size (Sim&Cure, France)17 18 and Ankyras (Galgo Medical SL, Spain) 19 20. Sim&Size provides a workflow similar to that of AneuGuide TM .…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available software with embedded geometrical deployment methods include Sim&Size (Sim&Cure, France)17 18 and Ankyras (Galgo Medical SL, Spain) 19 20. Sim&Size provides a workflow similar to that of AneuGuide TM .…”
Section: Discussionmentioning
confidence: 99%
“…To prevent this complication, a computational software-based simulation can be used to help select an appropriately sized stent. 30 Saglam et al 31 reported that intersection zone stenosis always occurs in the Y-stent configuration with laser-cut closed-cell designed stents and braided stents. Theoretically, the conformity to curved arterial geometry, wall apposition and neck coverage make the open-cell design superior to the closed design.…”
Section: Discussionmentioning
confidence: 99%
“…The use of computational stent sizing tools is proving its clinical value (6)(7)(8)(9). Accurate stent simulations provide additional information and a rationale for the choice of size and length of the device based on specific patient morphology.…”
Section: Introductionmentioning
confidence: 99%